Effects of the use of Documentary Videos in Teaching Setting-out in Nigerian Secondary Schools - Mohammed Auta; M. Giwa (Journal of Education and Vocational Research, 2020)
The purpose of the study was to determine the effect of the use of documentary videos in teaching setting-out in Nigerian secondary schools. One research question and one hypothesis guided the study. The study adopted Quasi-experimental research design. The population for the study was 16 ST 1 students from Government Technical Training School, Jalingo offering Building Construction subject. There was no sampling. The instrument for data collection was Setting-out Test (ST) developed by the researcher. The instrument was validated by three experts. Test re-test was used to establish the reliability of the instrument and a reliability coefficient of 0.83 and 0.87 was obtained for the traditional and documentary video teaching methods respectively. The ST 1 students were arranged in intact groups, A and B; treatment was given to the two groups. Group a students were taught using the traditional method while Group B students were taught using the documentary video. A Pre-Test and Post-test was administered on the two groups under examination condition. The data obtained were analyzed using mean, standard deviation for research question and analysis of covariance (ANCOVA) for the hypothesis. Findings from the study indicated that students taught Setting-out with documentary videos performed better than those taught with the traditional teaching method; and there was a significant difference in the performance of students taught Setting-out with documentary video and those taught with traditional teaching method. Based on the findings some recommendations were made